Alternative approaches to news: the role of media distrust, perceived network homophily, and interests in news topics - Segado-Boj, Francisco (2021)
This study focuses on three contemporary alternative users' attitudes to news previously detetected in the literature: 'News finds me', 'The information is out there' and 'I don't know what to believe. It analyzes the role of users' media distrust and social network homophily perception as predictors of each considered attitude. Secondly, the study also considers the effect of the mentioned attitude on user's interests in different news topics. Last, it compares the reciprocal influence of the aforementioned attitudes among them. A survey (n = 279) was developed among Spanish Facebook users. Data was analysed through multiple regression test. Results show that media distrust positively predicted “The Information Is Out There” but was not relevant in the cases of “News Finds Me” and “I Don’t Know What To Believe”. “News Finds Me” negatively predicted interest in hard news (domestic, international politics, and economy), and “The Information Is Out There” predicted interest in lifestyle news and stories about celebrities. Perceived network homophily was not predicted by any of the observed attitudes. A reciprocal influence was detected between “The Information Is Out There” and “News Finds Me” but no influence was identified from or to “I Don’t Know What To Believe”. We conclude that “The Information Is Out There” may have the same negative effects on political knowledge and participation that “News Finds Me” as it drives users away from hard news item and towards softer topics.